Green building technology : development of visible light harvesting self-cleaning surface - Yeow, Ronie Wai Leong. (2009)
TiO2 had been studied extensively in the development of self-cleaning glasses. However, due to its large band gap energy (Eg = 3.2 eV), pure TiO2 exhibits photocatalytic activity only under UV irradiation. In the current work, the incorporation of InVO4, which is a novel narrow band gap semiconductor (Eg = 2.0 eV), into TiO2 is anticipated to improve the photocatalytic activity of TiO2-InVO4 thin films under visible light. In our experiment, transparent TiO2-InVO4¬-coated glass substrates were synthesized using simple sol-gel method. XRD spectra showed that the TiO2-InVO4 samples are highly dispersed and consist of uniform anatase TiO2 nanocrystals. TiO2-InVO4 nanocomposites exhibited extended light absorbance in the visible light regime with a significant red shift in light absorption from 400 nm, which corresponds to pure anatase TiO2 thin films, to 565 nm corresponding to TiO2-InVO4 composite with 3.0 wt% InVO4 (10.0 mol% PEI). Besides that, TiO2-InVO4-coated glass substrates remained hydrophilic even after 30 days of storage in the dark. The TiO2-InVO4 thin films also exhibited high photocatalytic activity under visible light irradiation. Photo-induced decomposition of stearic acid for TiO2-InVO4 3.0 wt% InVO4 (10.0 mol% PEI) reached an average rate of 2.5 nm/h compared to those of TiO2, which is only 0.8 nm/h.